Plastic bronchitis: An unusual complication of acute chest syndrome in adult. (2017) - Feray, Sarah; Mora, Pierre; Decavele, Maxens; Pham, Tài; Hafiani, El Mahdi; Fartoukh, Muriel
Abstract: Plastic bronchitis is used to designate endobronchial plugs of rubber-like consistency that form into bronchial trees. It has been described in several diseases like asthma, cystic fibrosis, pulmonary infection, cyanotic congenital heart disease and in few young children with homozygous sickle cell disease. We report the first sickle cell adult case of plastic bronchitis during acute chest syndrome. He developed severe acute respiratory distress syndrome. This unusual presentation related to obstruction by voluminous casts may alert physicians to focus more on the bronchi in sickle cell patients. Realization of fiberoptic bronchoscopy to diagnose endobronchial injury and preventive measures such as fluidification of sputum at the early stage of thoracic vaso-occlusive crisis are essential.